Searching for TeV Gamma-Ray Emission from SGR 1935+2154 during Its 2020 X-Ray and Radio Bursting Phase - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Astrophysical Journal, 2021)
Magnetar hyperflares are the most plausible explanation for fast radio bursts (FRBs)-enigmatic powerful radio pulses with durations of several milliseconds and high brightness temperatures. The first observational evidence for this scenario was obtained in 2020 April when an FRB was detected from the direction of the Galactic magnetar and soft gamma-ray repeater SGR 1935+2154. The FRB was preceded by two gamma-ray outburst alerts by the BAT instrument aboard the Swift satellite, which triggered follow-up observations by the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observed SGR 1935+2154 for 2 hr on 2020 April 28. The observations are coincident with X-ray bursts from the magnetar detected by INTEGRAL and Fermi-GBM, thus providing the first very high energy gamma-ray observations of a magnetar in a flaring state. High-quality data acquired during these follow-up observations allow us to perform a search for short-time transients. No significant signal at energies E > 0.6 TeV is found, and upper limits on the persistent and transient emission are derived. We here present the analysis of these observations and discuss the obtained results and prospects of the H.E.S.S. follow-up program for soft gamma-ray repeaters.
CRIS-Team WoS Importer:2021-10-08